Impact of a Single Customs Territory in the East African Community on Tanzania's exports - Anne Kamau; Maureen Odongo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The implementation of a Single Customs Territory by East African Community countries is intended to ease the movement of goods across borders by cutting costs and time through harmonization and simplification of customs documents, removal of burdensome customs procedures, and automation of customs systems. Using descriptive statistics and an econometrics estimation method, this study examines the impact of a Single Customs Territory on Tanzania's exports from 2004 to 2018. The key findings reveal that Tanzania's merchandise exports to East African Community countries have remained low under the Single Customs Territory. Challenges persist as trade costs remain high and it takes a significant amount of time to export goods. Policy proposals include relaxation of border costs and time required, expeditious harmonization of customs systems and documentation, investment in cargo-related infrastructure, value addition of exports, and ratification of agreements.
Keywords: F13; F14; F15; 330; Single Customs Territory; trade costs; East African Community